Analisis Pengambilan Keputusan Pembiayaan Produktif (Murabahah) Melalui Prinsip 5C pada Bank Aceh Syariah Cabang Jeuram - Masykurah, Masykurah; Sartika, Dewi (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
In the financing practices of Bank Aceh Syariah Cabang Jeuram, problems with financing problems or bad credit are often encountered. To reduce this risk, banks carry out feasibility evaluations before approving financing requests from customers. This evaluation focuses on the application of the 5C principles, which include Character, Capacity, Capital, Collateral, and Economic Conditions, as a precautionary measure in dealing with debtors. All of these principles are considered important in the financing assessment process. This study adopted a field research method with a qualitative approach, where information and data were collected and explained through interviews and direct observation. The results of this research show that financing problems are often caused by customers' economic instability, and not due to mistakes by the marketing team in applying the 5C principles in financing evaluation.